KUALITAS KAYU LAPIS DARI DARI KOMBINASI KAYU AKASIA (Acacia auriculiformis) DAN SUNGKAI (Peronema canescens) (Plywood Quality from Acacia auriculiformis and Peronema canescens timbers): Sushardi - JHT, Admin (Jurnal Hutan Tropika, 2015)
ABSTRACTIn order to increase plywood production in Indonesia, utilization the timbers coming from forest community is very important. Some species that widely planted at the forest community in DI Yogyakarta are akacia (Acacia auriculiformis) and sungkai (Peronema canescens). This research was aimed to know the combination some veneers formed of acacia timber and sungkai timber with the urea formaldehide resurfaced adhesive to producing the high quality plywood. The combination treatments were veneers from acacia timber (S1), veneer from sungkai timber (S2), veneer-core from acacia timber and veneer – face – back from sungkai timber (S3), and veneer-core from sungkai timber and veneer – face – back from akasia timber (S4). The experiment used complete randomized design with the further test using Tukey procedure in processing data. The research result showed that the treatment of veneer-core from acacia timber, and veneer-face-back from sungkai timber with the 60 #/MSGGL resurfaced adhesive have the better physical and mechanical property than the other treatments. Despitefully, sungkai timber has more decorative wood and a high commercial value.Keywords: Acacia, plywood, sungkai, veneer